Proyecto de implementación de un nuevo sistema logístico integral a partir del 2009, para optimizar los procesos aduaneros dentro de un almacén temporal para la empresa inarpi s.a. - Cevallos, Xavier (2009)
Free trade Between countries is one of the most dominant and accelerated during the last decades, therefore the national economic development is closely linked to the facilities of trade